A search for gamma-ray emission from the Galactic plane in the longitude range between 37° and 43° - Aharonian, Felix A.; Akhperjanian, A. G.; Barrio, J. A.; Bernlöhr, Konrad; Bolz, O.; Hermann, G.; Heusler, A.; Hofmann, Werner; Konopelko, Alexander; Kornmeyer, H.; Kranich, D.; Krawczynski, Henric; et al. (Astronomy and astrophysics, 2001)
Using the HEGRA system of imaging atmospheric Cherenkov telescopes, a - region of the Galactic plane (-10o < b < 5o, - 38o < l < 43o) was surveyed for TeV - gamma-ray emission, both from point sources and of diffuse nature. The - region covered includes 15 known pulsars, 6 known supernova remnants - (SNR) and one unidentified EGRET source. No evidence for emission from - point sources was detected; upper limits are typically below 0.1 Crab - units for the flux above 1 TeV. For the diffuse gamma-ray flux from the - Galactic plane, an upper limit of 6.1*E-15 ph cm-2 - s-1 sr-1 MeV-1 was derived under the - assumption that the spatial distribution measured by the EGRET - instrument extends to the TeV regime. This upper flux limit is a factor - of about 1.5 larger than the flux expected from the ensemble of - gamma-ray unresolved Galactic cosmic ray sources.